Comparative readability of information on different treatment options for breast cancer, based on WeChat public accounts. - Bingyan Li; Jia Liu; Yuxi Zhang; Wenjuan Yang; Min Liu; Lunfang Xie (PLoS ONE)
Objective To evaluate and compare the readability of information on different treatment options for breast cancer from WeChat public accounts, propose targeted improvement strategies based on the evaluation of the results of the various treatment options, and provide a reference for producers of WeChat public accounts from which to write highly readable information regarding breast cancer treatment options. Methods With "breast cancer" as keywords in April 2021, searches were implemented on Sogou WeChat website (https://weixin.sogou.com/) and WeChat mobile app. The selected WPAs were aimed to provided breast cancer health information, and the four latest articles of each WPA were included in the evaluation. Two independent observers assessed the readability of the articles through the Suitability Assessment of Materials (SAM) tool, and compared the readability of information on different treatment options, i.e., surgical treatment, medical treatment, complementary and alternative medicine (CAM), and comprehensive treatment. Results A total of 136 articles on different types of breast cancer treatments from 37 WeChat public accounts were included in the present study. The median SAM score was 50 (IQR, 41-60). In terms of treatment options, the readability of articles in the CAM category scored higher in the content 75 (IQR, 63-81), learning stimulation and motivation 75 (IQR, 50-83) and cultural appropriateness 75 (IQR, 75-75) categories than in the medical and surgical treatment categories (P < 0.05). Additionally, the readability of articles in the CAM category scored higher in the cultural appropriateness 75 (IQR, 75-75) category than those for comprehensive and medical treatment (P < 0.05). Conclusions The overall readability of information on breast cancer treatment options in WeChat public accounts was in the lower portion of the "adequate" level. The readability of articles on medical treatment options is poor, especially on clinical trial articles, which could be improved in terms of content, graphics, learning stimulation, and motivation to make them more suitable for public reading.